Characterization of physicochemical, rheological, aroma, and sensory properties of spreadable processed cheese supplemented with chia, quinoa, and teff seeds - Buket Aydeniz Guneser; Barıs Aklale; Onur Guneser (Mljekarstvo, 2023)
The physicochemical, rheological, aroma, and sensory properties of spreadable processed cheese supplemented with chia, quinoa, and teff seeds were evaluated. The changes in proximate composition, color values, rheological parameters, volatile profile, sensory, and microbiological properties of the cheese samples stored at 4 °C for 90 days were assessed. Significant differences in the initial contents of dry matter, protein, and fat were observed among the cheese samples. The pH was affected by the storage time and type of added pseudocereal. Moreover, the storage time and type of pseudocereal interaction affected the titratable acidity and color parameters of the cheese samples. The water-soluble nitrogen content increased slightly in all cheese samples during storage. The cheese samples supplemented with pseudocereals exhibited a pseudoplastic behavior. The consistency index of the cheese samples ranged from 2.277 to 2.550 Pa.sn, and the flow behavior index ranged from 0.528 to 0.665. The counts of total coliform and yeast-mold in all cheese samples were <1 log CFU/g cheese, and the counts of total mesophilic aerobic bacteria ranged from 2.21 log CFU/g cheese to 2.76 log CFU/g cheese. A total of 27 volatile compounds, consisting of acids, aldehydes, ketones, esters, and terpenes, were identified in the cheese samples. The amounts of butanoic acid, hexanoic acid, octanoic acid, and nonanoic acid in all cheese samples were higher than that of other volatiles, with the amounts ranging from 639 µg/kg to 3284 µg/kg, 711.20 µg/kg to 2723.27 µg/kg, 187.60 µg/kg to 722.71 µg/kg, and 75.42 µg/kg to 206.02 µg/kg, respectively. The most preferred cheese in terms of sensory properties was the control sample, followed by the SCT, SCQ, and SCC samples.